2017
DOI: 10.1080/17538068.2017.1385575
|View full text |Cite
|
Sign up to set email alerts
|

College students and HIV testing: cognitive, emotional self-efficacy, motivational and communication factors

Abstract: Most college students have never been tested for HIV, even though they regularly have unprotected sex and multiple sex partners. Theory-based research addressing factors influencing HIV testing among college students is limited. This study explored this topic via a conceptual framework that integrates the health belief model with emotion and communication factors. Data was collected with a sample of four focus group panels, including two male and two female groups (N = 52). Transcripts for the seven discussion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 52 publications
1
26
1
1
Order By: Relevance
“…Social approval and emotional support can help to overcome perceived fear and stigma related to planning on HIV testing. 22 …”
Section: Discussionmentioning
confidence: 99%
“…Social approval and emotional support can help to overcome perceived fear and stigma related to planning on HIV testing. 22 …”
Section: Discussionmentioning
confidence: 99%
“…A large percentage of students who were not interested in testing, or were unaware of the fact that HIV testing was available free of charge in Kosovo, was observed. Lin et al (2017) reported that perceived invulnerability among students and students' low emotional self-efficacy represent important barriers to HIV testing. The HIV testing rate in this study was markedly low compared with that reported in other countries, such as the United States (9.3%-47.5%), Cameroon (40%), Greece (28.3%), Ireland (17.5%) and Iran (13.1%) (Gullette & Lyons, 2006;Inungu et al, 2009;Shokoohi et al, 2013;Choudhary et al, 2015;Nubed & Akoachere, 2016;Kann et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…They were willing to know their HIV infection status, which prompted the emergence of detection behaviors. Some studies had also pointed out that the feeling of guilt and the fear of HIV infection caused by conducting high-risk sexual behaviors would also prompt the detection of HIV [42,43].…”
Section: Additive Interaction Between Recreational Drug Use and Uai Omentioning
confidence: 99%